AKTUALISASI AJARAN TEOLOGI SOSIAL DALAM UPACARA PIODALAN DI PURA DALEM SAKENAN - Komang Heriyanti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The temple is a sacred place to get closer to God for Hindus. One of the temples including DangKahyangan in Bali is Dalem Sakenan Temple. Dalem Sakenan Temple is a heritage temple fromDang Hyang Nirartha who came to Bali during the reign of Dalem Waturenggong. DalemSakenan Temple is a Shiva-Buddhist temple. In ancient times, getting to Dalem Sakenan Templewas not easy, because you had to take a boat across the ocean to get to the mangrove forest.However, at this time, to get there is already road access so that Hindus can easily get there. Theimplementation of the Piodalan ceremony at Dalem Sakenan Temple has a social theologicalaspect. This can be seen from before the Piodalan ceremony was carried out by Hindus togetherngayah preparing Piodalan at Dalem Sakenan Temple. All Hindus who take part in ngayahactivities, together help each other to prepare the things needed during the Piodalan ceremony.The ngayah activity was not only attended by Hindus who only came from one area, but alsocame from various regions because the performers of Dalem Sakenan Temple came from all overBali. Research on the actualization of social theology in the piodalan ceremony at the DalemSakenan Temple uses qualitative research so that everything that is in the field can bedescribed. The data were obtained through observation, interviews, and document studies. Fromthis data, it can be concluded how far aspects of social theology are implemented by Hindus atDalem Sakenan Temple.